Reduplication and doubling contrasted: implications for the structure of the DP and the AP - Alexiadou, Artemis (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
This paper examines adjectival reduplication in Chinese which is contrasted with determiner doubling in Germanic. It shows that two superficially different phenomena in two genetically unrelated languages are sensitive to similar properties. Both environments support an analysis of adjectives in terms of restrictive relative clauses and strengthen the case for decomposing the adjective.